STRATEGI DERADIKALISASI MELALUI KONSEP MIZĀH FĪ SUNNAH AL-NABI - Mohammad Zainul Wafa (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2020)
Radicalism is a threat that every nation has experienced. The first characteristic of radicals is a textualist and dogmatic, the second, extreme and militant, the third, takfiri, or judging infidel with the other people who opposite with them. So, this research discusses the concept of a prophet’s pleasantry as a practice of moderation to avoid radicalization. In it there is good purpose and message. The study deploys content analysis to answer how the concept of having fun could be used to de-radicalize radical attitude and behaviors. The study finds that pleasantry concept of prophet which is contextual, righteous, and egalitarian, has several purposes including al-tasliyah (consolation), al-ta‘allum (learning), izalāh al-qalq (relieve the anxiety), mulāṭifah wa mulayyinah (show the softness), and taṭyīb al-kalām (pleasant words). Therefore, through mizāh fī al-sunnah concept expected realization of deradicalization, tolerance, and moderation of Muslims in the sphere of nation and state.